Establishment and characterization of a new cell line from koi brain (Cyprinus carpio L.). Issue 2 (24th October 2017) - Wang, Y; Zeng, W; Wang, Q; Li, Y; Bergmann, S M; Zheng, S; Ren, Y; Liu, C; Chang, O; Lee, P
Abstract: A novel permanently growing brain cell line from koi ( Cyprinus carpio L.) (KB cell line) was established, and its suitability for detection of koi herpesvirus (KHV) was demonstrated in this study. The KB cell line was optimally maintained at 27°C in Leibovitz's L‐15 medium supplemented with 10% foetal bovine serum (FBS). It was subcultured more than 100 times, and chromosome analysis revealed that 51.54% of KB cells at passage 80 maintained the abnormal diploid chromosome number 2 n  = 96 while the modal chromosome number was 2 n  = 100. The cell line was cryopreserved in liquid nitrogen at −196°C and was recovered from storage after 1 year with good cell viability and vitality. The results of virus isolation demonstrated that KB cells were susceptible to KHV, which was shown by the presence of an obvious cytopathic effect and abundant virus particles. The viral titres of KHV in KB reached 10 5.73 TCID50 /0.1 ml within 7 days. Immunofluorescence and Western blot assays confirmed that KB replicated KHV. The newly established KB cell line will serve as a useful tool to elucidate KHV disease (KHVD) pathogenesis.